TEKS DAN KONTEKS DALAM KAJIAN TRADISI LISAN ANGKOLA - wati, Erna Ika (AIN Padangsidimpuan, 2014)
ABSTRAKLanguage is unique related to text and context. Context represent text and inturn, text present context. Both text and context canneot be separated one and each other to understand and produce meaning. No one language is better than others. Every language is good, better and unique in text and context. It can be seen the enrichment of local tradition on so long in time in Angkola to be identity and cannot be changed.Kata Kunci: Teks dan Konteks, Kajian Tradisi Lisan, Angkola